2019
DOI: 10.1016/j.yebeh.2019.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary levels among people living with epilepsy: A systematic review and meta-analysis

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Physical activity is an element of lifestyle, which is important for maintaining health. Although participants with epilepsy as well as healthy participants in the study were moderately active, patients with epilepsy spent more time during the day sitting and less often performed intensive and moderate physical activity during the week, what is consistent with other ndings [70]. Lower physical activity may be affected by low occupational activity of epileptics compared to healthy people, 36.7% compared to 82.9%, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Physical activity is an element of lifestyle, which is important for maintaining health. Although participants with epilepsy as well as healthy participants in the study were moderately active, patients with epilepsy spent more time during the day sitting and less often performed intensive and moderate physical activity during the week, what is consistent with other ndings [70]. Lower physical activity may be affected by low occupational activity of epileptics compared to healthy people, 36.7% compared to 82.9%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Lower physical activity may be affected by low occupational activity of epileptics compared to healthy people, 36.7% compared to 82.9%, respectively. The latest meta-analysis of population studies shows that further research is needed before speci c recommendations on physical activity in people with epilepsy are formulated [70]. Among patients with epilepsy, but not in the control group, a positive relationship was found between the level of physical activity and serum concentration of vitamin D3.…”
Section: Discussionmentioning
confidence: 99%
“…Role of Exercise People with epilepsy are less likely to engage or even intend to engage in physical activities [42][43][44]. In a Norwegian sample, the proportion of people never exercising was significantly greater for an epilepsy cohort than the average population [45].…”
Section: 4mentioning
confidence: 98%
“…In general, several studies reported that physical activity has a positive influence on seizure frequency and severity Vancampfort, Ward, & Stubbs, 2019). As a result, attitudes regarding sports and epilepsy have changed considerably in recent decades, and presently, the risk of convulsive seizures during sports practice is minimal in cases of well-managed epilepsy (van Gorp et al, 2019).…”
Section: Discussionmentioning
confidence: 99%